Pengaruh Pengalaman Pelanggan dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan - Nuraeni, Ani; Putri, Dewi Yolanda (Mansion: Management and Business on Kebangsaan, 2025)
Introduction: In the beauty clinic industry, where competition intensifies rapidly, customer loyalty becomes a decisive factor for sustainability. This study investigates the influence of customer experience and service quality on loyalty at Aestica Beauty Clinic in Bandung. Background Problems: The clinic experienced a decline in customers from 1,189 in 2023 to 700 in 2024, raising the key research question: To what extent do customer experience and service quality affect customer loyalty, both partially and jointly? Novelty: While service quality has often been studied, few empirical studies have quantitatively examined its combined effect with customer experience in the beauty clinic sector, particularly in Indonesia. This research offers new evidence in a context marked by growing competition and shifting customer expectations. Research Methods: Using a quantitative approach, the study surveyed 87 customers through random sampling. Data were analyzed with multiple linear regression using SPSS 23, supported by validity and reliability testing to ensure robust measurement. Finding/Results: The results demonstrate that both customer experience and service quality significantly and positively affect loyalty. Customer experience explains 76.8% of the variance, service quality contributes 19.5%, and together they account for 96.3% of customer loyalty. Conclusion: The findings highlight that improving customer experience and maintaining consistent service quality are essential strategies for sustaining loyalty in beauty clinics. These insights suggest that businesses in this sector should prioritize personalized interactions, responsive service, and consistent quality to strengthen customer retention and competitiveness.